Synthesis and utility of fluorogenic acetoxymethyl ethers - Lavis, Luke D. (2011)
Phenolic fluorophores such as fluorescein, Tokyo Green, resorufin, and their derivatives are workhorses of biological science. Acylating the phenolic hydroxyl group(s) in these fluorophores masks their fluorescence. The ensuing ester is a substrate for cellular esterases, which can restore fluorescence. These esters are, however, notoriously unstable to hydrolysis, severely compromising their utility. The acetoxymethyl (AM) group is an esterase-sensitive motif that can mask polar functionalities in small molecules. Here, we report on the use of AM ether groups to mask phenolic fluorophores. The resulting profluorophores have a desirable combination of low background fluorescence, high chemical stability, and high enzymatic reactivity, both in vitro and in cellulo. These simple phenyl ether-based profluorophores could supplement or supplant the use of phenyl esters for imaging biochemical and biological systems.